Do income smoothing, capital management, signaling, and pro-cyclicality exist through loan loss provisions? Evidence from Malaysia commercial banks - Noor Shahieda, Mohd Hishamuddin (2014)
Loan loss provisions are the main accrual expenses charged to bank income statement to absorb loan losses arising from loans default. The main purpose of this dissertation is to examine whether Malaysia commercial banks use loan loss provisions as a tool in income smoothing, capital management, and signaling. This dissertation also examines whether pro-cyclicality exists through loan loss provisions in Malaysia. Covering period from 2002 to 2012, the results indicate that Malaysian commercial banks do smooth income through loan loss provisions but no evidence for capital management. This dissertation also finds no evidence for Malaysia commercial banks to signal private information to outsiders. Although there is a negative coefficient between loan loss provisions and GDP, the results demonstrate that Malaysian commercial banks do not involve in pro-cyclical behavior through loan loss provisions. The results also show that the global financial crisis in 2008 does not affect loan loss provisions of Malaysian commercial banks.